REGULASI DAN PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) RUMAH SAKIT DI PROPINSI SUMATERA BARAT - Bambang Ristiono; Nizwardi Azkha (Faculty of Public Health, Andalas University, 2009)
The study is related to the implementation of regulation’s policy on hospital safety and occupational health in West Sumatera. Hospital will implement regulation that local government established if there is effective mechanism. Regulation is an authoritative ride regarding to detail procedures that declare on local government policy. The study aims to describe regulation policy of health department on behalf of Local Government for the implementation of hospital safety and occupational health in order to see effective regulation factors to make hospital obedient and will to implement regulation policy that established. Methods: The method of the study was case study with explorative descriptive. Dependent variable in the study was hospital safety and occupational health in West Sumatera, while the Independent variable was regulation policy of local government in implementing hospital safety and occupational health with factors in it, that cover sanction and reward, watch, regulation focus, human resource, financial, commitment, public control, and transparency. Objective: The study was obtained in Health Department and district hospital in West Sumatera that covers 6 district hospitals, ie. 2 hospitals with 12 accredited statuses, 2 hospitals with 5 accredited statuses, 2 hospitals with unaccredited status, and private hospital. Subject of the study was hospital manager and hospital manager in health Department of West Sumatera Province and district/city. Data were collected by dept. interview and spreading questionnaire that was obtained because of the difficulty of location and the busy of respondents. The result of the study shows that regulation of hospital safety and occupational health is weak, low commitment of hospital management toward hospital safely and occupational health, in order to make effective regulation of hospital safety and occupational health, it need the support of human resource, financial, sanction and reward, transparency, and public control. In order to make hospital safety and occupational health implemented well, health department of West Sumatera Province has to: complete the existing rule and socialized it to all hospitals, presence government and hospitals’ presence, increasing hospital's commitment and support to make effective regulation. The result of study wished to be used local government as a reference in implementing and maintaining regulation policy of hospital safety and occupational health, especially in West Sumatera in the future.